A Risk Stratification Model for Metastatic Lymph Nodes of Papillary Thyroid Cancer: A Retrospective Study Based on Sonographic Features - Ni, Xiaofeng; Xu, Shangyan; Zhan, Weiwei; Zhou, Wei (Frontiers in Endocrinology, 2022)
Background: Papillary thyroid carcinoma (PTC) has a high probability of cervical lymph node (LN) metastasis. The aim of the study was to develop an ultrasound risk stratification model to standardize the diagnosis of metastatic LNs of PTC. Methods: Patients with suspicious thyroid nodules who underwent US examination and US guided fine-needle aspiration for cervical LNs were retrospectively collected. Univariate and multivariate logistic regression analysis were performed to assess independent risk factor of metastatic LNs. According to the OR value of correlated indicators in logistic regression analysis, a risk stratification model was established. Results: A total number of 653 LNs were included. The independent risk factors of metastatic LNs were Long-axis diameter/short-axis ≤ 2 (OR=1.644), absence of hilum (OR=1.894), hyperechogenicity (OR=5.375), calcifications (OR=6.201), cystic change (OR=71.818), and abnormal flow (OR=3.811) (P<0.05 for all). The risk stratification model and malignancy rate were as follows: 0-2 points, malignancy rate of 10.61%, low suspicion; 3-5 points, malignancy rate of 50.49%, intermediate suspicion, ≥6 points, malignancy rate of 84.81%, high suspicion. The area under the receiver operating characteristic curve for the model was 0.827 (95% CI 0.795-0.859). Conclusions: Our established risk stratification model can effectively evaluate metastatic LNs in the patients with suspicious thyroid nodules, and it might provide a new strategy choice for clinical practice.